2012
DOI: 10.4236/gm.2012.22006
|View full text |Cite
|
Sign up to set email alerts
|

Kozeny-Carman Equation and Hydraulic Conductivity of Compacted Clayey Soils

Abstract: The saturated hydraulic conductivity of a soil is the main parameter for modeling the water flow through the soil and determination of seepage losses. In addition, hydraulic conductivity of compacted soil layers is critical component for designing liner and cover systems for waste landfills. Hydraulic conductivity can be predicted using empirical relationships, capillary models, statistical models and hydraulic radius theories [1]. In the current research work the reliability of Kozeny-Carman equation for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 5 publications
0
16
0
2
Order By: Relevance
“…Although the estimated relation curve of Yukselen-Aksoy and Kaya [46] is near the measured SSA value, this curve is for a given LL, below which the SSA will be overestimated and above which the SSA will be underestimated. Steiakakis et al [43] underestimate the SSA value, and other empirical relationships overestimate the SSA value; the overestimation error can be approximately 10 times the actual value. According to Equation (1), the permeability is k ∝ (1/S 2 ).…”
Section: Estimation Of Specific Surface Area For Loessmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the estimated relation curve of Yukselen-Aksoy and Kaya [46] is near the measured SSA value, this curve is for a given LL, below which the SSA will be overestimated and above which the SSA will be underestimated. Steiakakis et al [43] underestimate the SSA value, and other empirical relationships overestimate the SSA value; the overestimation error can be approximately 10 times the actual value. According to Equation (1), the permeability is k ∝ (1/S 2 ).…”
Section: Estimation Of Specific Surface Area For Loessmentioning
confidence: 95%
“…The physical properties of soil are not isolated and often associated with each other. Many researchers have found that the SSA of clay is closely related to the LL, e.g., finding a linear relationship between the SSA and LL [23,24,[37][38][39][40][41][42] or that the reciprocal of the SSA has a linear relationship with the reciprocal of the LL [21,32,43], and a good power function relationship between the SSA and LL [38,[44][45][46][47]].…”
Section: Definition and Application Of Specific Surface Area (Ssa) Inmentioning
confidence: 99%
“…Such models have often been used to determine the permeability of scaffolds . The Kozeny–Carman equation, first proposed by Kozeny and later refined by Carman, is commonly used to predict permeability in various solids . This equation has many forms and is based on classical Navier–Stokes fluid mechanics.…”
Section: Methodsmentioning
confidence: 99%
“…6 The Kozeny-Carman equation, first proposed by Kozeny and later refined by Carman, is commonly used to predict permeability in various solids. [30][31][32][33] This equation has many forms and is based on classical Navier-Stokes fluid mechanics. The Kozeny-Carman equation can be expressed to give n, the hydraulic conductivity (m/s), as follows: Given that…”
Section: Mathematical Modeling Of Permeabilitymentioning
confidence: 99%
“…In this paper, we have made what we believe are reasonable assumptions about how rapidly the transport of fluid, platelets, and proteins is reduced by changes in the platelet density within the thrombus, and we explored the consequences of these assumptions on the model’s dynamics as well as the sensitivity of model results to different choices of the reduced-transport functions. In particular, we look at two different permeability functions; the one we used in [29] and the Kozeny-Carman relation [19] used, for example, for predicting flow through soils [41]. The two permeability functions behave quite differently in terms of how quickly the permeability decreases as the solid (here bound platelet) volume fraction increases.…”
Section: Introductionmentioning
confidence: 99%